KAJIAN LITERATUR PELAKSANAAN GOOD GOVERNANCE MELALUI PROGRAM CETTAR DI PROVINSI JAWA TIMUR - DHARMAWAN, AWAN; Zulharman; Makbul, Moh; Kabunggul, Orce; Muhaimin (Journal of Law and Administrative Science, 2025)
This research is an interdisciplinary study that aims to see how the implementation of good governance in East Java through the CETTAR program. This research was conducted using a qualitative method with a descriptive approach and using secondary data sources from several scientific publications that were collected and then reviewed and deepened so that conclusions could be drawn. The results of the study show that the implementation of good governance has been carried out optimally which was achieved in the 4th year after the CETTAR program was implemented in 2019, especially with the use of Digital technology. This research is expected to be a reference for other researchers who want to conduct in-depth research related to the CETTAR program in East Java Province.